The Creative Approach for Promoting Violin Performing Arts in China in the 20th Century - Chen, Fang; Thoard, Manoon (International Journal of Multidisciplinary in Management and Tourism, 2022)
The composer Mr. Chen Gang is one of the creators of Chinese violin music. Through literature research, this study learned about Chen Gang’s living environment during the creation of The Golden Furnace. He combined Chinese national music materials with Western composition techniques and integrated western traditional violin playing skills into the Chinese nationalized music language, which played an essential role in exploring the road of Chinese violin nationalization. This paper also explains and reveals the steps involved in the creative work of the violin master that remains very popular in China. The violin tune "Golden Furnace " was adapted and created by the famous composer Mr Chen Gang. Although this tune has the brand of the times in the unique historical period, its beautiful melody, gorgeous technique and full of passion all make it worthy of further study.